Integrating a Virtual Learning Environment into a Second Year Accounting Course: Determinants of Overall Student Perception - Wells, P.; De Lange, Paul; Fieger, P. (Wiley-Blackwell Publishing Asia, 2008)
Rapid acceptance of, and changes in, information technology are revolutionizingthe way educators teach and students learn. This study reports on the use ofBlackboard as a tool for creating a virtual learning environment (VLE). Responsesfrom undergraduate accounting students in New Zealand provide data on the useof the VLE as a learning aid. Findings suggest that the students have openlyembraced the VLE and support its adoption by faculty members in other courses.However, students appear unwilling to actively participate in two-way onlineactivities. This has implications for faculty contemplating the adoption of aVLE in their courses.